Juridical Analysis of Fiduciary Security over Crypto Assets: Reconstructing Possession, Enforcement Mechanisms, and the Urgency of a Central Custodian in Ensuring Certainty of Collateral Value - Devi Mutiara Sanni (Law Research Review Quarterly, 2026)
The development of crypto assets as part of the digital economic transformation has generated new legal implications within Indonesia’s secured transactions framework, particularly concerning their potential use as objects of fiduciary security. This study aims to analyze the mechanisms of possession and execution of fiduciary security over crypto assets under the Indonesian legal system and to examine the urgency of establishing a central custodian to ensure legal certainty and the stability of the collateral value. This research employs a normative juridical method using statutory and conceptual approaches. Legal materials were obtained through library research on legislation, legal literature, and previous studies, which were analyzed qualitatively and prescriptively. The findings indicate that crypto assets juridically satisfy the characteristics of intangible movable property possessing economic value and, therefore, may theoretically serve as objects of fiduciary security. However, the existing fiduciary security regime has not adequately accommodated the decentralized nature of blockchain technology, particularly with regard to digital possession based on private keys, mechanisms for digital seizure, and the execution of security interests over crypto assets. Furthermore, the high volatility of crypto asset values and the absence of a centralized controlling authority create risks to collateral value certainty and creditor protection. Accordingly, legal reconstruction is required through regulatory reform and the establishment of a central custodian as a digital asset custodial institution responsible for ensuring control, supervision, value stability, and the effective execution of fiduciary security involving crypto assets. KEYWORDSFiduciary Security; Crypto Assets; Central Custodian.